Distinctions and similarities of cell bioenergetics and the role of mitochondria in hypoxia, cancer, and embryonic development - Jezek, Petr; Plecitá-Hlavatá, Lydie; Smolková, Katarína; Rossignol, Rodrigue (The international journal of biochemistry & cell biology, 2010)
In this review we compare situations under which the major cellular role of mitochondria, oxidative phosphorylation (OXPHOS), is transiently suppressed. Two types of cellular bioenergetics exist, related to the predominance of glycolysis either disconnected or fully connected to OXPHOS: i) "glycolytic" phenotype, when the glycolytic end-product pyruvate is marginally used for OXPHOS; and, ii) OXPHOS phenotype with fully developed and active OXPHOS machinery consuming all pyruvate. A switch to glycolytic phenotype is typically orchestrated by gene reprogramming due to AMP-activated protein kinase, hypoxia-induced factor (HIF), NFkappaB, mTOR, and by oncogenes. At normoxia a continuous hydroxylation of HIF1alpha prolines by prolyl hydroxylase domain enzymes (PHDs) and asparagines by factor-inhibiting HIF (FIH) occurs, resulting in HIF1alpha polyubiquitination/degradation. With O(2) below a threshold level (<5% O(2)) cytosolic H(2)O(2) raises and oxidizes Fe(2+) of PHDs and FIH, inactivates them, thus stabilizing HIFalpha and upregulating transcription of specific genes. The source of H(2)O(2) burst (not manifested in isolated mitochondria) is the respiratory chain Complex III Q(O) site. Frequently hypoxic microenvironment of malignant tumors stimulates HIF-mediated conversion to the glycolytic state, nevertheless OXPHOS tumors also exist. The glycolytic mode predominates prior to implantation phase of embryonic development, hence in embryonic stem cells. Finally, a "Poderoso hypothesis" is discussed, predicting repetitive conversions to a transient glycolytic mode after a meal and concomitant insulin signaling. Accordingly, insulin stimulates mitochondrial NO synthase simultaneously with cellular glucose intake. The elevated NO diminishes respiration by inhibiting cytochrome c oxidase. Type 2 diabetes may result from the accumulated impact of such nitrosative/oxidative stress.
Keywords: energetický metabolismus; Mitochondria; hypoxie buňky; Neoplasms; Oxidative Phosphorylation; Embryonic Development; signální transdukce; Signal Transduction; oogeneze; Animals; lidé; Energy Metabolism; Cell Hypoxia; Humans; zvířata; embryonální vývoj; nádory; oxidativní fosforylace; mitochondrie; Oogenesis